La guerra de los desposeídos. Honduras y El Salvador, 1969 - C. J. (ECA: Estudios Centroamericanos, 1981)
No hay resúmenes disponibles.ECA Estudios Centroamericanos, Vol. 36, No. 398, 1981: 1156-1157.